A comprehensive assessment of four-satellite QZSS constellation: navigation signals, broadcast ephemeris, availability, SPP, interoperability with GPS, and ISB against GPS. Issue 382 (2nd January 2022) - Li, XuanPing; Pan, Lin; Yu, Wenkun; Dai, Wujiao; Li, Yanjie; Peng, Hui
Abstract : In this study, a comprehensive assessment of four-satellite Quasi-Zenith Satellite System (QZSS) constellation is conducted, including the quality of navigation signals, the accuracy of broadcast ephemeris, the availability of satellite constellation, the performance of single point positioning (SPP), the interoperability with GPS, and the inter-system bias (ISB) against GPS. Regarding the signal quality, no significant difference between QZSS and GPS can be found. The signal-in-space ranging error (SISRE) of QZSS satellites is 0.59–0.62 m. The service rate of QZSS-only positioning is 69.8–77.8% in QZSS service areas. A positioning accuracy of 5.70, 3.20 and 6.99 m in east, north and up directions can be achieved for the QZSS-only SPP. After introducing QZSS observations into GPS-only SPP processing, the positioning accuracy can be slightly improved. The ISB with a short-term stability of 1.75 ns behaves like systematic biases, and thus cannot be ignored in the GPS/QZSS combined SPP.